Simplifying
F(x) = -0.05(x2 + -26x + -120)
Multiply F * x
xF = -0.05(x2 + -26x + -120)
Reorder the terms:
xF = -0.05(-120 + -26x + x2)
xF = (-120 * -0.05 + -26x * -0.05 + x2 * -0.05)
xF = (6 + 1.3x + -0.05x2)
Solving
xF = 6 + 1.3x + -0.05x2
Reorder the terms:
-6 + -1.3x + xF + 0.05x2 = 6 + 1.3x + -0.05x2 + -6 + -1.3x + 0.05x2
-6 + -1.3x + xF + 0.05x2 = 6 + -6 + 1.3x + -1.3x + -0.05x2 + 0.05x2
Combine like terms:
6 + -6 = 0
-6 + -1.3x + xF + 0.05x2 = 0 + 1.3x + -1.3x + -0.05x2 + 0.05x2
-6 + -1.3x + xF + 0.05x2 = 1.3x + -1.3x + -0.05x2 + 0.05x2
1.3x + -1.3x = 0.0
-6 + -1.3x + xF + 0.05x2 = 0.0 + -0.05x2 + 0.05x2
-6 + -1.3x + xF + 0.05x2 = -0.05x2 + 0.05x2
-0.05x2 + 0.05x2 = 0.00
-6 + -1.3x + xF + 0.05x2 = 0.00